French Canadian cross-cultural adaptation of CAPTSure©, an index for the Clinical Assessment of Post-Thrombotic Syndrome in children - Marie-Claude P; Angelika Stavrakoukas; Gina Wong; Raoul Santiago; Laura Avila (SpringerOpen, 2023)
Abstract Purpose Post-thrombotic syndrome (PTS) is the most common complication of deep venous thrombosis (DVT). The index for the Clinical Assessment of Post-Thrombotic Syndrome in children (CAPTSure©) is a clinical tool for the diagnosis and severity rating of PTS in pediatric patients. The purpose of this study was to translate and adapt CAPTSure© for French-speaking patients. Methods We conducted a cross-sectional study to perform linguistic and cultural adaptation of CAPTSure©, using a rigorous translation process followed by cognitive debriefings in twenty French-speaking pediatric patients aged up to 18 years old with a history of upper or lower extremity DVT at least 6 months prior. Results Forward and backward translations were used to produce a pre-final French version of CAPTSure©, followed by cognitive debriefings in twenty participants (median age: 11.5 years, 55% male, median CAPTSure© score: 26). The participants felt that the questionnaire was thorough, with an adequate length. Eight out of fourteen (57%) items in the LE questionnaire and 7/12 (58%) of the items in the UE questionnaire were modified following participants' and a multidisciplinary expert committee's input, leading to the final French version of CAPTSure©. Conclusions CAPTSure© was successfully adapted for French-speaking pediatric patients. This will ease the diagnosis and severity rating of PTS in children in clinical practice and allow international research collaborations for additional non-English-speaking patients.